Analysis of Indonesian DIKTI and DIKTIS Higher Education Curriculum Development Policy - Latif, Muhammad Sabri; Ariarta, Aliffany Pualam; Muid, Abdul; Latif, Abdul; Suti’ah, Suti’ah; Aziz, Abdul (Yayasan Indonesia Emerging Literacy Education, 2024)
This research analyzes educational policies related to the development of the higher education curriculum in Indonesia, which is an important component in the educational process. The basis for curriculum development is regulated in higher education laws and government regulations. This research aims to provide insights and processes in curriculum development in Indonesia, as well as complement previous research that defines educational policies related to higher education curriculum development at the Ministry of Education and Culture, higher education curriculum development policies (DIKTI) and educational curriculum development policies for Islamic Religious Higher Education. (DICTIS) in Indonesia. The method used in this research uses the Library Research type of literature review, by collecting and analyzing books, articles and related references. The results of data analysis highlight the role of the Ministry of Education and Culture and the Directorate General of Islamic Higher Education in curriculum development. The curriculum development process involves in-depth study, evaluation, consultation, and analysis of job market needs. The curriculum development policy aims to improve the quality of higher education, ensure the relevance of the curriculum to the demands of the times, and ensure equal access to education. Challenges in curriculum development include rapid changes in the world of science, limited resources, and multidimensional needs. This research provides an understanding of higher education curriculum development policies in Indonesia, as well as contributing to the improvement and refinement of existing policies to support the development of quality human resources.